2017
DOI: 10.1590/2359-3997000000291
|View full text |Cite
|
Sign up to set email alerts
|

Use of cinacalcet and sunitinib to treat hypercalcaemia due to a pancreatic neuroendocrine tumor

Abstract: SUMMARYNeuroendocrine tumors (NETs) can secrete hormones, including ectopic secretions, but they have been rarely associated with malignant hypercalcemia. A 52-year-old man with a history of diabetes mellitus was diagnosed with a pancreatic tumor. A pancreatic biopsy confirmed a well-differentiated pancreatic NET (pNET). The patient subsequently developed liver metastasis and hypercalcemia with high 1,25 OH vitamin D and suppressed parathyroid hormone (PTH) levels. Hypercalcemia was refractory to chemotherapy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Surprisingly, our patient started responding to cinacalcet, with a reduction in her albumin-adjusted total serum calcium levels to 2.79 mmol/L. In the other reports in which cinacalcet has been used for the treatment of paraneoplastic hypercalcaemia, the tumours involved have been neuroendocrine tumours, breast cancer, lung cancer and renal cell carcinoma 6 12–15…”
Section: Discussionmentioning
confidence: 66%
“…Surprisingly, our patient started responding to cinacalcet, with a reduction in her albumin-adjusted total serum calcium levels to 2.79 mmol/L. In the other reports in which cinacalcet has been used for the treatment of paraneoplastic hypercalcaemia, the tumours involved have been neuroendocrine tumours, breast cancer, lung cancer and renal cell carcinoma 6 12–15…”
Section: Discussionmentioning
confidence: 66%
“…We furthermore completed our research by analyzing the references of the selected papers (see Figure 1 ). We finally assessed 78 papers for a total of 114 patients for eligibility (see Table 1 ) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ,…”
Section: Resultsmentioning
confidence: 99%
“…A recent investigation showed that tyrosine kinase inhibitor drugs, such as sunitinib, could decrease the calcium level in some cases [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%